2023
DOI: 10.3390/mi14030532
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polymethylpentene, an Oxygen Permeable Thermoplastic, for Long-Term on-a-Chip Cell Culture and Organ-on-a-Chip Devices

Abstract: The applicability of a gas-permeable, thermoplastic material polymethylpentene (PMP) was investigated, experimentally and analytically, for organ-on-a-chip (OoC) and long-term on-a-chip cell cultivation applications. Using a sealed culture chamber device fitted with oxygen sensors, we tested and compared PMP to commonly used glass and polydimethylsiloxane (PDMS). We show that PMP and PDMS have comparable performance for oxygen supply during 4 days culture of epithelial (A549) cells with oxygen concentration st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…With this low gas permeability, the gas bubbles present do not pass through the COC material and will eventually leave the channel carried by the flowing fluid. In PDMS, the gas permeability is reported to be between 523 barrer [47] and 733 barrer [48] at 35-37 °C. In PDMS, it was observed that bubbles formed continuously through the entire length of the channel.…”
Section: Temperature Tolerance Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this low gas permeability, the gas bubbles present do not pass through the COC material and will eventually leave the channel carried by the flowing fluid. In PDMS, the gas permeability is reported to be between 523 barrer [47] and 733 barrer [48] at 35-37 °C. In PDMS, it was observed that bubbles formed continuously through the entire length of the channel.…”
Section: Temperature Tolerance Testsmentioning
confidence: 99%
“…With this low gas permeability, the gas bubbles present do not pass through the COC material and will eventually leave the channel carried by the flowing fluid. In PDMS, the gas permeability is reported to be between 523 barrer [47] and 733 barrer [48] at 35-37 • C. In PDMS, it was observed that bubbles formed continuously through the entire length of the channel. Due to the high gas permeability of PDMS, the air trapped inside the channel can pass through the material, but it also be renewed due to the device being in contact with air, allowing a continuous formation of bubbles.…”
Section: Temperature Tolerance Testsmentioning
confidence: 99%